Cyanidin-3-O-Glucoside Induces the Apoptosis of Human Gastric Cancer MKN-45 Cells through ROS-Mediated Signaling Pathways - Wei Sun; Nai-Dan Zhang; Tong Zhang; Yan-Nan Li; Hui Xue; Jing-Long Cao; Wen-Shuang Hou; Jian Liu; Ying Wang; Cheng-Hao Jin (Molecules, 2023)
Cyanidin-3-O-glucoside (C3G), an active ingredient in anthocyanins, mainly exists in dark cereals. C3G was investigated for its effect on human gastric cancer (GC) cells, together with its molecular mechanism. The CCK-8 assay results showed that C3G had significant antiproliferative effects on GC cells, but it had little effect on normal cells. Western blot and flow cytometry results showed that C3G regulated the reduction of mitochondrial membrane potential and arrested the cell cycle in the G2/M phase through the AKT signaling pathway, causing the cells to undergo apoptosis. Additionally, in MKN-45 cells, C3G markedly raised intracellular reactive oxygen species (ROS) levels. The wound healing assay and Transwell assay results showed that MKN-45 cell migration was significantly inhibited. Western blot results showed that the expression of E-cadherin protein was upregulated and the expressions of β-catenin, N-cadherin, and Vimentin were downregulated. Additionally, following N-acetylcysteine treatment, the expression levels of these proteins were reduced. In conclusion, C3G caused MKN-45 cells to undergo apoptosis; arrested the cell cycle in the G2/M phase; hindered cell migration; and activated the MAPK, STAT3, and NF-κB signaling pathways, by inducing an increase in ROS levels. Thus, C3G may be a promising new medication for the treatment of GC.